The Impact of Medical Tourism Industry for the Hospital Services and Marketing Activities: A Systematic Review - Taufik, Nadya Aviliyani; Sulistiadi, Wahyu (UI Scholars Hub, 2018)
The relationship between the health industry and tourism has produced what is called medical tourism which is one of the largest and fastest growing service industries in the world and is a profitable business for the destination country. To capture the many medical tourists it is necessary to recognize the vital factors that influence the decision of medical tourists to choose the destination country by implementing marketing strategies and good health services. Using Systematic Review with PRISMA method retrieved from online database such as PubMed, and Google Scholar using a keyword “Medical tourism” AND “hospital services” AND “marketing”. The end of this search got 7 journals. India, Singapore and Thailand are the three main medical tourist destinations worldwide with the advantages of each offered. Medical tourism is strongly influenced by patient satisfaction with the quality of health and quality of services. A good marketing strategy plays a very important role in introducing medical tourism to medical tourists. With interesting websites and social media, you can capture patients without considering other factors. Not to forget also patient satisfaction is very influential on the return or absence of patients to do medical tours to the country.